Synthesis of CoFe2O4@Cu3(BTC)2 nanocomposite as a magnetic metal–organic framework. (1st December 2019) - Saemian, Tahoura; Gharagozlou, Mehrnaz; Hossaini Sadr, Moayad; Naghibi, Sanaz
Graphical abstract: The nanocomposite of CoFe2 O4 @ Cu3 (BTC)2 was synthesized based on the Pechini sol–gel technique. CoFe2 O4 and Cu3 (BTC)2 could be seen in the XRD pattern. SEM and TEM images contain some similar nanoparticles with uniform size and shape. Photoluminescence behavior of the composite compound was better than that of CoFe2 O4 nanoparticles. Incredible values were measured for specific surface area and pore volume which are 438 m 2 /g and 0.67 cm 3 /g, respectively. The magnetic response of the nanocomposite was achieved about 20 emu/g, which is high enough to utilize for collecting this material after applying in different situations. Abstract: An exquisite method with high efficiency has been utilized to synthesized a composite material based on Cu3 (BTC)2 as a metal–organic framework (MOF) as well as CoFe2 O4 nanoparticles. This is a novel method and presented throughout this manuscript for the first time. For this aim, the composite compound was fabricated via Pechini sol–gel method by using iron nitrate, methacrylic acid, ethanol, copper nitrate, and trimesic acid. The obtained compound due to its magnetic properties could be an appropriate candidate for smart materials, and medical applications. The results showed that the composite compound contains both Cu3 (BTC)2 as a MOF and also CoFe2 O4 . The obtained features in microscopic observations approved the formation of homogenous nanoparticles which are not similar to column-shape-particle of the MOF. Although UV absorption of the composite compound declined, both photoluminescence and specific surface area improved rather than CoFe2 O4 nanoparticles. Such a compound with 438 m 2 /g surface area, 0.67 cm 3 /g pore volume, and tremendous magnetic response of 20 emu/g seems to be valuable enough for more consideration.